Why weight for happiness? Correlates of BMI and SWB in Australia. Issue 6 (November 2015) - Robertson, Sharon; Davies, Matthew; Winefield, Helen
Summary: Despite our best medical and behavioural strategies, the physical and mental health of the overweight and obese remains compromised. In an effort to improve treatment outcomes, research has begun to focus on (1) specific BMI categories, and (2) subjective well-being (SWB), a broad construct exploring how we evaluate and experience our lives. Positive psychology is concerned with SWB, through the application of variables associated with health, happiness and optimal functioning. To date, research exploring the relationship between BMI categories and SWB is lacking for community based Australians. This study employed a cross-sectional design using an online survey method ( n  = 260). SWB and related variables were assessed over five BMI categories including normal, overweight, and obese classes one, two and three. Main findings suggest the class two and three obese demonstrated significantly lower scores on flourishing in comparison with the normal and overweight. The class three obese also demonstrated higher depression, and lower scores on agency and positive affect in comparison with the normal and overweight. Furthermore class two and three obese reported lower scores on pathways thinking than the overweight. Results provide preliminary support for the hypothesis that a lack of SWB may contribute to or maintain atypical BMI. Implications for treatment interventions are discussed.